Changing indications and techniques for corneal transplantations at a tertiary referral center in Turkey, from 1995 to 2014 - Altay Y (Dove Medical Press, 2016)
Yesim Altay, Ayse Burcu, Gozde Aksoy, Evin Singar Ozdemir, Firdevs Ornek Department of Ophthalmology, Ankara Training and Research Hospital, Ankara, Turkey Background: Indications for corneal transplantation in developed and developing nations differ according to the different spectrum of corneal disease in each country. Objective: The purpose of this study is to analyze the changing indications and surgical techniques for corneal transplantation over the past 20 years at a tertiary referral center in Turkey. Methods: We retrospectively reviewed the records of patients who underwent keratoplasty from January 1995 to December 2014 (between 1995 and 2004, period 1, and between 2005 and 2014, period 2). Patients’ demographic data, indications for corneal transplantation, and the type of surgery were recorded. Results: The number of keratoplasties performed ranged from 548 in period 1 to 782 in period 2. Between 1995 and 2004, the leading indications were keratoconus (34.1%), bullous keratopathy (17%), and non-herpetic corneal scar (13.3%), and between 2005 and 2014, they were keratoconus (33.8%), corneal stromal dystrophy (14.2%), and bullous keratopathy (12.7%). All the keratoplasties performed in the 1995–2004 period were penetrating keratoplasty (PKP). During the period 2005–2014, PKP accounted for 93%, automated lamellar keratoplasty 5.8%, and deep anterior lamellar keratoplasty 1.2% of all corneal transplantations. Conclusion: Keratoconus was the leading indication for keratoplasty in both periods. In the 2005–2014 period, corneal stromal dystrophy increased significantly. All the keratoplasties performed in period 1 and 93% of all keratoplasties performed in period 2 were PKP. Keywords: corneal transplantation, indication, keratoconus, keratoplasty technique, penetrating keratoplasty